Bronchial carcinoma and hyperkeratosis palmaris et plantaris. Issue 663 (January 1981) - Powell, F.; Mackey, J. P.
Abstract : A 44-year-old man who presented with recent onset hyperkeratosis palmaris et plantaris was found to have a carcinoma of the bronchus.